Episodic zircon age spectra mimic fluctuations in subduction. Issue 1 (December 2018) - Domeier, Mathew; Magni, Valentina; Hounslow, Mark; Torsvik, Trond
Abstract Decades of geochronological work have shown the temporal distribution of zircon ages to be episodic on billion-year timescales and seemingly coincident with the lifecycle of supercontinents, but the physical processes behind this episodicity remain contentious. The dominant, end-member models of fluctuating magmatic productivity versus selective preservation of zircon during times of continental assembly have important and very different implications for long-term, global-scale phenomena, including the history of crustal growth, the initiation and evolution of plate tectonics, and the tempo of mantle outgassing over billions of years. Consideration of this episodicity has largely focused on the Precambrian, but here we analyze a large collection of Phanerozoic zircon ages in the context of global, full-plate tectonic models that extend back to the mid-Paleozoic. We scrutinize two long-lived and relatively simple active margins, and show that along both, a relationship between the regional subduction flux and zircon age distribution is evident. In both cases, zircon age peaks correspond to intervals of high subduction flux with a 10–30 Ma time lag (zircons trailing subduction), illuminating a possibly intrinsic delay in the subduction-related magmatic system. We also show that subduction fluxes provide a stronger correlation to zircon age distributions than subduction lengths do, implying that convergence rates play a significant role in regulating the volume of melting in subduction-related magmatic systems, and thus crustal growth.